2019
DOI: 10.4102/sajpsychiatry.v25i0.1230
|View full text |Cite
|
Sign up to set email alerts
|

The psycho-social and clinical profile of women referred for psycho-legal evaluation to forensic mental health units in South Africa

Abstract: Background: There is a paucity of research on women offenders in the South African context, particularly those referred for forensic psychiatric observation. Little is known about their life histories, the nature of their offences or the psycho-social contexts that enable, or are antecedents to, women’s criminal offending.Aims: This research study, the largest of its kind in South Africa, examined the psycho-social contexts within which women offenders referred for psychiatric evaluation come to commit offence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…As for the type of crime, a study comparing male and female homicide offenders with SMI reported a four to one ratio of males to females [ 16 ]. In contradiction, other studies found that women with SMI committed more serious crimes than men, more frequently including arson (27.5% women, 12.4% men) and homicide (28.1% women, 15.1% men; [ 31 ], and were primarily admitted for such crimes [ 32 , 33 ]. Female offenders with SMI were found to engage in more self-harming (women 22–33%, men 8–13%) and to have comorbid personality disorders [ 34 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…As for the type of crime, a study comparing male and female homicide offenders with SMI reported a four to one ratio of males to females [ 16 ]. In contradiction, other studies found that women with SMI committed more serious crimes than men, more frequently including arson (27.5% women, 12.4% men) and homicide (28.1% women, 15.1% men; [ 31 ], and were primarily admitted for such crimes [ 32 , 33 ]. Female offenders with SMI were found to engage in more self-harming (women 22–33%, men 8–13%) and to have comorbid personality disorders [ 34 ].…”
Section: Introductionmentioning
confidence: 96%
“…Several studies found female offender patients with SMI to be more likely to target close family members [ 16 , 31 ], which has not been found in female offenders without SMI. In contrast to non-offending women with SSD [ 5 , 6 ], many female offender patients with SMI did abuse alcohol (34–48%) or illicit drugs (35–44%), suffered from socio-economic adversity [ 32 , 33 ] and had a higher number of forensic and general psychiatric hospitalizations than men [ 34 ]. The few studies explicitly focusing on female offender patients with SMI [ 31 34 ] did not distinguish between different mental disorders and often presented descriptive accounts only.…”
Section: Introductionmentioning
confidence: 99%
“…The demographic profile of the seven participants was in keeping with a recent review of 573 female offenders across six forensic mental health institutions in South Africa by Nagdee et al (17). This study found that the majority of offenders were aged 21–50 years old, which is similar to this study where 86% of the participants fell within this age group.…”
Section: Discussionmentioning
confidence: 84%
“…Within the South African context, a recent large retrospective study of 573 accused female offenders referred for observation under the Criminal Procedures Act to six forensic mental health institutions showed that there were 175 crimes committed against children, and of those, 66% were biological children. Furthermore, it was found that 52% of these women had disclosed having a prior psychiatric illness, with 30% having committed filicide (17). In another unpublished study done at Sterkfontein Hospital, Gauteng, South Africa, 42% of referred cases of child homicide were found to have a history of psychiatric illness (18).…”
Section: Introductionmentioning
confidence: 99%
“…It did not look at changes over time, but found that over the 12-year period in review, murder was the most common index offence and that there were high rates of psychotic and mood-spectrum disorders present in their sample. 12 Another study that examined the factors associated with recidivism at Sterkfontein Hospital, South Africa, found that substance use disorder, antisocial personality disorder and having assault as an index offence were associated with a higher risk of recidivism. 13 …”
Section: Introductionmentioning
confidence: 99%